Definicja retoryczna jako sposób wprowadzania nazw wartości i antywartości w "Monitorze" = Rhetorical definition as a way of introducing value and antithesis values in "Monitor" - Dawidziak-Kładoczna, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, I discuss the rhetorical definition as a frequently used "Monitor" - a journal that went beyond twenty years in enlightenment. Rhetorical definitions are not lexicographical because they do not place emphasis on the relation sign - the non-linguistic realm, but it emphasizes the linguistic relationship - the language user.
Keywords: "Monitor" - czasopismo; nazwy wartości; definicja retoryczna; perswazja; metafora; value names; "Monitor" magazine; rhetorical definition; persuasion; metaphor